Nonlinear behaviour of waffle slab under concentrated load / Ahmad Rashidi Allias - Allias, Ahmad Rashidi (1997)
This study is to investigate the nonlinear behaviour of prestressed waffle slab under concentrated load by using computer software namely ANalysis SYStem version 5.0. Three specimens of prestressed waffle slabs, WSCL1 (4 equal wafffes), WSCI-2 (9 equal waffles), and WSCL3 (16 equal waffles) are modeled and analysed using finite element analysis (FEA). The nonlinear behaviour of the three prestressed waffle slabs are compared wtth the results of experiments conducted by Khairul Amali ( July 1991). Results are interpreted in term of load-deflection relationship, stress distribution and stress-strain behaviour. The behaviour of the waffle slab specimens were bounded by the influences of transducer locations and numbers of ribs involved in the quadrant. ïn this study, the finite element analysis considered similar points to which deflections and strains are measured. The overall strength of the three specimens relied totaily on the prestressed rib existence and locations and the FE models produced similar results as reported earlier (Khairul Amali, July 1991).